The P gene product of hepatitis B virus is required as a structural component for genomic RNA encapsidation. - Bartenschlager, R (1990)
Encapsidation of the pregenomic RNA into nucleocapsids is a selective process which depends on specific RNA-protein interactions. The signal involved in the packaging of the hepatitis B virus (HBV) RNA pregenome was recently defined as a short sequence located near the 5' end of that molecule (Junker-Niepmann et al., EMBO J., in press), but it remained an open question which viral proteins are required. Using a genetic approach, we analyzed whether proteins derived from the HBV P gene play an important role in pregenome encapsidation. The results obtained with point mutations, deletions, and insertions scattered throughout the P gene clearly demonstrate that (i) a P gene product containing all functional domains is required both for the encapsidation of HBV pregenomic RNA and for packaging of nonviral RNAs fused to the HBV encapsidation signal, (ii) known enzymatic activities are not involved in the packaging reaction, suggesting that P protein is required as a structural component, and (iii) P protein acts primarily in cis, i.e., pregenomic RNAs from which P protein is synthesized are preferentially encapsidated.